Participation of calcium and calmodulin in the formation of acetylcholine receptor clusters (The Rockefeller University Press, 1984)
The formation of acetylcholine receptor (AChR) clusters can be experimentally induced in cultured Xenopus myotomal muscle cells by positive polypeptide-coated latex beads (Peng, H.B., P.-C. Cheng, and P.W. Luther, 1981, Nature [Lond.], 292:831-834). This provides a simple procedure for studying the cellular process of AChR clustering. In this study, the involvement of calcium and calmodulin in this process was examined. A deprivation in extracellular calcium by calcium-free medium or by the addition of calcium antagonists such as divalent cations Co2+ and Ni2+ (1-5 mM) or organic compounds verapamil and D-600 (0.1-0.5 mM) suppressed the formation of AChR clusters induced by the latex beads in a largely reversible manner. Antagonists against calmodulin, including trifluoperazine (1-5 microM) and the naphthalene sulfonamide W-7 (20 microM), also suppressed AChR clustering. However, the effect of W-7 was much weaker than that of trifluoperazine (TFP). Although the formation of AChR clusters is inhibited by these drugs, the stability of the existent clusters is relatively insensitive to them. These data suggest that the clustering of AChR involves a Ca2+ and calmodulin- activated process. Immunofluorescence studies using an antibody against calmodulin indicate that calmodulin is diffusely distributed in the cytoplasm in addition to its localization at the I-bands. Thus I propose that a local rise in intracellular calcium caused by a locally applied stimulus, exemplified here by the polypeptide-coated latex beads, may trigger the formation of AChR clusters. Furthermore, the cellular machinery for this process may involve calmodulin and is diffusely distributed in the muscle cell.